2019
DOI: 10.1016/j.ijid.2019.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The role of tuberculosis control institutes in delivering tuberculosis information to domestic migrants in China: A multi-level analysis of a nationwide cross-sectional survey

Abstract: The aim of this study was to understand how tuberculosis (TB) control institutes raise awareness of TB among domestic migrants in China, specifically whether migrants have received TB information and how they received it. Methods: This multi-level analysis included both county-level data and individual-level data covering 31 provinces in mainland China. Multi-level logistic models were used to explore the factors associated with receiving TB information. Results: This analysis included 205 990 migrants from 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Furthermore, this region is combined with several undeveloped provinces, which are in critical lack of health resources, leading to delays in detection and diagnosis, as well as to low vaccine coverage of infectious diseases. Furthermore, some studies also found that residents who lived in this region lack self-protection awareness [39,40]. So, in this region, the health sector should maintain sufficient health resources supply and improve residents' health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this region is combined with several undeveloped provinces, which are in critical lack of health resources, leading to delays in detection and diagnosis, as well as to low vaccine coverage of infectious diseases. Furthermore, some studies also found that residents who lived in this region lack self-protection awareness [39,40]. So, in this region, the health sector should maintain sufficient health resources supply and improve residents' health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other research, adults bore the highest burden of PTB, with individuals aged 65 and above exhibiting the highest incidence rates [ 9 , 23 ]. Our results also indicate that farmers faced a higher risk of PTB, a trend potentially influenced by limited health services and patient management in rural areas [ 23 ], compounded by a lack of disease prevention awareness contributing to PTB transmission [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, available literature showed that the prevention and control of active TB in MP meant an enormous challenge globally. MP typically has lower awareness of TB, causing potential delay diagnosis [ 31 33 ]. Besides, Non-adherence to anti-TB treatment is common among MP, which may increase the risk of TB transmission and the development of drug resistance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%